COURT DECISION NUMBER 6/PID.SUS-TPK/PN PGP IN THE PERSPECTIVE OF THE JUSTICE THEORY ESPECIALLY ACCORDING TO THOMAS HOBBES - Apribilli, Apribilli; Vincentius Anggoro Wahyo Putro; Giovano Gumansalangi; G. Widiartana (Domus Legalis Cogitatio, 2025)
This study raises the problem that the Pangkalpinang District Court Decision Number 6/Pid.Sus-TPK/PN Pgp against the crime of obstruction of justice in the crime of corruption is considered contrary to the value of justice, because the sanctions imposed on the defendant with the losses suffered by the state are not balanced. Based on the gap between legal norms and legal facts that have been stated, this research aims to criticize the decision through the perspective of the theory of justice according to Thomas Hobbes, in addition to discussing it from the perspective of social justice theory and the purpose of punishment, especially integrative theory. This research used normative juridical legal research methods with a conceptual approach that is connected based on secondary legal materials, namely the theory of justice put forward by Thomas Hobbes. The results of this research stated that the Pangkalpinang District Court Decision Number 6/Pid.Sus-TPK/PN Pgp did not fulfill the criteria of the theory of justice stated by Thomas Hobbes, which states that the judge must consider the public interest harmed by Toni Tamsil's actions. The decision also contradicts the integrative theory, which emphasizes that punishment aims to avenge the perpetrator's actions of the crime and a preventive effort so that the crime does not recur. On the other hand, the decision also hurts the social justice aspect in society and is contrary to the state foundation of Pancasila, namely social justice for all Indonesian people.